Współistnienie zespołu Brooke'a-Spieglera z łuszczycą zwykłą - opis przypadku - Olga Michałowska; Katarzyna Łukowska; Anna Kozłowska (Termedia Publishing House, 2011)
Introduction. Brooke-Spiegler syndrome is a rare, autosomal dominantdisease. It is characterized by appearance of cylindromas, trichoepitheliomasand spiradenomas. Multiple cylindromas most frequently arelocalized on the scalp (turban tumours).Objective. To present coexistence of Brooke-Spiegler syndrome withpsoriasis vulgaris - that determined the mode of psoriasis therapy.Case report. A 59-year-old man was admitted to the hospital due toexacerbation of psoriasis vulgaris. The patient had many tumours onthe scalp and nodules around the nose and eyebrows. Histopathologicalinvestigation revealed multiple cylindromas and trichoepitheliomas.On the basis of the clinical picture and histopathological investigation,diagnosis of Brooke-Spiegler syndrome was established.Additionally, atypical nevus on the skin of the abdomen was recognised. Psoriatic lesions were treated with systemic acitretin and topicalointments.Conclusions. In the presented case, treatment of psoriasis vulgaris wasdetermined by coexistence of adnexal tumours and atypical nevus.